Immediate psychological impacts on the inmates of a quarantine-isolation facility in North Kashmir: a pilot study - Rashid, Suhail; Singh, Charanjit; Masood, Syed; Khan, Waheeda (International Journal of Research in Medical Sciences, 2020)
Background: During the current COVID-19 pandemic as part of various control measures quarantine-isolation facilities have been setup throughout India. To the best of our knowledge no study has been done so far on the mental health aspects of the inmates from Kashmir region. Methods: This was a questionnaire based qualitative cross sectional pilot study. A cohort of 301 inmates (196 males and105 females) consented and completed the study questionnaire from March 2020 to June, 2020. The relevant data was statistically analyzed. Results: Short lived negative impacts were seen in a sizeable number of patients. These negative correlates of mental health remained manageable as we followed the guidelines of MOHFW. Only a small percentage of 4% (11 of 301) inmates needed psychiatric consultation and treatment. However they safely completed their mandatory stay period in the facility. Conclusions: Based on the results of our study, we conclude that optimum medical care during the pandemic remains the main focus and rightly so, but nevertheless mental health domain needs to be equally strengthened at the facilities in particular for short term impacts and the community in general for long term impacts.